(untitled) (Terr@ Plural, 2019)
The physical and populational growth of medium-sized Brazilian cities have been characterized by their peripheral expansion, resulting in urban discontinuity and huge social, demographic, and economic disparities. Thus, this study identified free spaces in different areas of the city of Campina Grande and analyzed the sites with potential for future interventions that balance the poor distribution of free spaces for public use among the neighborhoods. It is proposed to reflect on the importance of the production of these spaces in the urban configuration starting from the problems and potentialities. From the results obtained, it was observed that important areas are without due legal protection by the urbanistic and environmental legislation. Given the current front directed to the intense production of real estate, coupled with the non-protection of such areas may strengthen a new urban amplification that will promote several negative impacts, to the detriment of absenteeism of land and environmental policies and the relations and stimuli between public and private agents. Such factors will influence the discontinuous urban abjunction, constructive integration, the threat of environmentally fragile areas and the poor quality of life of the population.